Safe return to rugby - in the context of the COVID-19 pandemic - Falvey, E.; Mathema, P.; Horgan, M.; Raftery, M. (2020)
This is a resource developed by World Rugby to help everyone in the rugby community during the COVID-19 pandemic and to guide a safe return to rugby activities. The first section provides information to everyone involved in the game including players, coaches, support and administrative staff. The second section provides a framework around which Unions can prepare policies and guidelines for return to activity that are appropriate to their local setting. This is a live document, that will be updated regularly, as this fast-evolving situation continues to change and so it should be referred to frequently to stay abreast of changesand developments. Who should read this document? This document is for the rugby community. Players, coaches, support staff, administrators -we are all part of society and most of the measures needed to combat COVID-19 start in the community and at home. Viral infection does not differentiate between people or locations. Strict observance of measures at work and at team facilities may be undone at home or in social situations. Wewill look at some of the specifics we all need to take care of in our daily life.Unions should use this framework to create polices for return to activity within their own jurisdiction. In doing so, Unions need to be sure to comply with local laws (including health & safety, employment and COVID-19-specific legislation) and any policies implemented by government or local authorities. Unions should monitor changes to such legislation and policies and amend their own policies as required to ensure that the rugby community in their jurisdiction is applying best practice and complying with local requirements.